The effect of radiation damage on anomalous absorption in the TEM - Scruby, L; Titchmarsh, J; Jenkins, M (2004)
In-situ electron irradiation of Si at 400keV was performed to determine the variation of two-beam absorption parameters by the method of Hashimoto. Corresponding theoretical sensitivity studies were performed to assess limitations of experimental errors. No significant variations in parameters were revealed. Possible reasons for this are discussed.